Physiological effects of temperature on turfgrass tolerance to amicarbazone. Issue 4 (13th August 2014) - Yu, Jialin; McCullough, Patrick E; Grey, Timothy
Abstract BACKGROUND Amicarbazone effectively controls annual bluegrass (Poa annua L.) in bermudagrass [Cynodon dactylon (L.) Pers. × C. transvaalensis Burtt‐Davy] and tall fescue (Festuca arundinacea Schreb.) with spring applications, but summer applications may excessively injure tall fescue. The objective of this research was to investigate physiological effects of temperature on amicarbazone efficacy, absorption, translocation and metabolism in annual bluegrass, bermudagrass and tall fescue. RESULTS At 25/20 °C (day/night), annual bluegrass absorbed 58 and 40% more foliar‐applied amicarbazone than bermudagrass and tall fescue, respectively, after 72 h. Foliar absorption increased at 40/35 °C in all species, compared with 25/20 °C, and tall fescue had similar absorption to annual bluegrass at 40/35 °C. At 6 days after treatment, annual bluegrass metabolized 54% of foliar‐applied amicarbazone, while bermudagrass and tall fescue metabolized 67 and 64% respectively. CONCLUSION Tall fescue is more tolerant to amicarbazone than annual bluegrass at moderate temperatures (≈25/20 °C) owing to less absorption and greater metabolism. However, tall fescue susceptibility to amicarbazone injury at high temperatures (40/35 °C) results from enhanced herbicide absorption compared with lower temperatures (25/20 °C). Bermudagrass is more tolerant to amicarbazone than annual bluegrass and tall fescue owing to less herbicide absorption, regardless of temperature. © 2014 Society of Chemical Industry